Country gets limited state arts funding - Wildermuth, Todd (Raton, NM Raton Range, 1995)
Article is about two out of five Colfax County groups which requested funding form the state and how much each group did or did not receive.
Newspaper article
Master list item # 113
File location is in the Raton file Cabinet
Keywords: Raton Art and Humanities Council; New Mexico Arts Commission; Arts Division Planning and Budget Committee; Moreno Valley Writer's Guild; New Mexico Boys School; Old Pass Gallery; Shuler Theater; Music from Angel Fire; State Funding for arts; Financial Rewards; Live Performance Funding; Art Funding; Raton, New Mexico